The Lawyer's Guide to Legal Process Improvement. (2014) - Alman MacDonagh, JD, Catherine; Kathuria, Rick A; Smith, Antony; Rechtschaffen, Scott; Kimbro, Stephanie; Craig, Kim R; Baker, Andrew M; Hanson, Tim; Thompson, Simon; Millard, Robert; Bull, Chris; Wasson, Lann; et al.
No abstract available